Antibody-based therapies for idiopathic pulmonary fibrosis. (2nd July 2020) - Sgalla, Giacomo; Flore, Mariachiara; Siciliano, Matteo; Richeldi, Luca
ABSTRACT: Introduction: Pirfenidone and nintedanib have been the first agents demonstrating to slow down the progressive functional decline in patients with Idiopathic Pulmonary Fibrosis (IPF). Antibody-based therapies with precise molecular targets have been largely investigated over the last decade in IPF as alternative or complementary treatments, in the hope to ameliorate the relentless fibrotic process of IPF. Areas covered: In this review, we summarize the available evidence on two groups of monoclonal antibodies tested in IPF: those directed against known fibrogenic factors and matrix components, and those developed to antagonize the inflammation and immunity pathways. While the latter have failed to demonstrate any clinical efficacy in IPF so far, the anti-CTGF pamrevlumab has been recently proved to be capable of slowing down functional decline as compared to placebo, prompting further investigation. Expert opinion: Despite most trials on antibody-based therapies in IPF provided so far unsatisfying results, the therapeutic development in this field should continue to be pursued to deliver a more personalized treatment approach in the future, which is not currently offered by available treatment options. A more careful trial designing and the use of valid predictive markers of response to treatment are required to enhance effectiveness of future trials.